Popular Psychology versus Scientific Evidence: Love Languages’ Factor Structure and Connection to Marital Satisfaction - Edwin Adrianta Surijah; Ni Made Mitha Prasetyaningsih; Supriyadi Supriyadi (Psympathic : Jurnal Ilmiah Psikologi, 2020)
Love is an essential part of human experience and love languages have been studied to validate its factors’ structures to explain what makes people feel loved. The current study addresses the gap that love research shall not rely on student samples and it needs to measure the actual outcome of love languages. This study aims to gather empirical evidence for love languages’ factor structure and its relation to the outcome variable. The method for this study is a quantitative survey with 250 couples reported their love languages using a rating-scale and forced-choice scale. The data analysis examined the factor structure of the love languages model and estimated the association between love languages compatibility and marital satisfaction. The factorial analysis showed that the five factors solution was not supported and love languages compatibility did not affect couples’ marital satisfaction. This result brought discussions on how popular psychology concepts need to be under the scrutiny of scientific investigation and that different contexts may have different factors on what makes people feel loved.